Multiple functions of G protein-coupled receptor kinases - Watari, Kenji (BioMed Central, 2014)
Desensitization is a physiological feedback mechanism that blocks detrimental effects of persistent stimulation. G protein-coupled receptor kinase 2 (GRK2) was originally identified as the kinase that mediates G protein-coupled receptor (GPCR) desensitization. Subsequent studies revealed that GRK is a family composed of seven isoforms (GRK1–GRK7). Each GRK shows a differential expression pattern. GRK1, GRK4, and GRK7 are expressed in limited tissues. In contrast, GRK2, GRK3, GRK5, and GRK6 are ubiquitously expressed throughout the body. The roles of GRKs in GPCR desensitization are well established. When GPCRs are activated by their agonists, GRKs phosphorylate serine/threonine residues in the intracellular loops and the carboxyl-termini of GPCRs. Phosphorylation promotes translocation of β-arrestins to the receptors and inhibits further G protein activation by interrupting receptor-G protein coupling. The binding of β-arrestins to the receptors also helps to promote receptor internalization by clathrin-coated pits. Thus, the GRK-catalyzed phosphorylation and subsequent binding of β-arrestin to GPCRs are believed to be the common mechanism of GPCR desensitization and internalization. Recent studies have revealed that GRKs are also involved in the β-arrestin-mediated signaling pathway. The GRK-mediated phosphorylation of the receptors plays opposite roles in conventional G protein- and β-arrestin-mediated signaling. The GRK-catalyzed phosphorylation of the receptors results in decreased G protein-mediated signaling, but it is necessary for β-arrestin-mediated signaling. Agonists that selectively activate GRK/β-arrestin-dependent signaling without affecting G protein signaling are known as β-arrestin-biased agonists. Biased agonists are expected to have potential therapeutic benefits for various diseases due to their selective activation of favorable physiological responses or avoidance of the side effects of drugs. Furthermore, GRKs are recognized as signaling mediators that are independent of either G protein- or β-arrestin-mediated pathways. GRKs can phosphorylate non-GPCR substrates, and this is found to be involved in various physiological responses, such as cell motility, development, and inflammation. In addition to these effects, our group revealed that GRK6 expressed in macrophages mediates the removal of apoptotic cells (engulfment) in a kinase activity-dependent manner. These studies revealed that GRKs block excess stimulus and also induce cellular responses. Here, we summarized the involvement of GRKs in β-arrestin-mediated and G protein-independent signaling pathways.